Elaborations on Corallopyronin A as a Novel Treatment Strategy Against Genital Chlamydial Infections - Loeper, Nathalie; Graspeuntner, Simon; Ledig, Svea; Kaufhold, Inga; Hoellen, Friederike; Schiefer, Andrea; Henrichfreise, Beate; Pfarr, Kenneth; Hoerauf, Achim; Shima, Kensuke; Rupp, Jan (Frontiers in Microbiology, 2019)
Ascending Chlamydia trachomatis infection causes functional damage to the fallopian tubes, which may lead to ectopic pregnancy and infertility in women. Treatment failures using the standard regimens of doxycycline and azithromycin have been observed. We tested the polyketide-derived α-pyrone antibiotic Corallopyronin A (CorA) that inhibits the bacterial DNA dependent RNA polymerase and has strong activity against various extracellular and some intracellular bacteria. Extensive testing in cell culture infection models and in an ex vivo human fallopian tube model under different oxygen concentrations was performed to assess the anti-chlamydial efficacy of CorA at physiological conditions. CorA showed high efficacy against C. trachomatis (MICN/H: 0.5 µg/mL for serovar D and L2), C. muridarum (MICN/H: 0.5 µg/mL) and C. pneumoniae (MICN/H: 1 µg/mL) under normoxic (N) and hypoxic (H) conditions. Recoverable inclusion forming units were significantly lower already at 0.25 µg/mL for all tested Chlamydiae. CorA at a concentration of 1 µg/mL was also effective against already established C. trachomatis and C. pneumoniae infections (up to 24 h.p.i.) in epithelial cells, while efficacy against C. muridarum was limited to earlier time points. A preliminary study using a C. muridarum genital infection model revealed corresponding limitations in the efficacy. Importantly, in an ex vivo human fallopian tube model, the growth of C. trachomatis was significantly inhibited by CorA at concentrations of 1-2 µg/mL under normoxic and hypoxic conditions. The overall high efficacies of CorA against C. trachomatis in cell culture and an ex vivo human fallopian tube model under physiological oxygen concentrations qualifies this drug as a candidate that should be further investigated.